Differential Cross-section Measurements for Deuteron Elastic Scattering on 11B. Issue 1 (1st October 2022) - Tsakiris, Th; Cosic, D; Dimitrakopoulos, N; Kokkoris, M; Krmpotić, M; Lagoyannis, A; Maragkos, F; Provatas, G; Ziagkova, A
Abstract: The implementation of boron in several fields, such as in the creation of p-type semiconductors in electronics, has created the need for the accurate quantitative determination of its depth profile concentrations in near surface layers of various matrices. In the framework of IBA techniques, a combination of Elastic Backscattering Spectroscopy (EBS), along with Nuclear Reaction Analysis (NRA), has been proposed in order to address the current needs for boron depth profiling, based on the use of a proton beam. Deuterons offer superior mass resolution with respect to protons, having similar stopping power values, but, unfortunately, the lack of experimental datasets concerning the deuteron elastic scattering on boron impedes their use. Thus, in the present work, the first set of measurements for the 11 B(d, d0 ) differential cross sections covering the Ed, lab =1300-1860 keV energy range for the backscattering angles of 150°, 160° and 170° was carried out. The study was conducted at the 5.5 MV Tandem Accelerator of the Institute of Nuclear and Particle Physics, in the National Center of Scientific Research "Demokritos", Athens, Greece. The target was a thin, self-supporting aluminum foil, upon which a thin nat B (isotopic ratio: 11 B 80.1%, 10 B 19.9%) layer was deposited using the sputtering technique at RBI, Zagreb, Croatia, followed by the evaporation of an ultra-thin layer of 197 Au on top for wear protection and normalization purposes. The outgoing particles were detected using 6 Silicon Surface Barrier (S.S.B.) detectors and the differential cross sections for the elastic scattering were determined from the resulting spectra via the relative measurement technique.